Effects of Vitamin D Supplementation on Bone Turnover Markers: A Randomized Controlled Trial - Schwetz, Verena (Nutrients, 2017)
Bone turnover markers (BTMs) are used to evaluate bone health together with bone mineral density and fracture assessment. Vitamin D supplementation is widely used to prevent and treat musculoskeletal diseases but existing data on vitamin D effects on markers of bone resorption and formation are inconsistent. We therefore examined the effects of vitamin D supplementation on bone-specific alkaline phosphatase (bALP), osteocalcin (OC), C-terminal telopeptide (CTX), and procollagen type 1 N-terminal propeptide (P1NP). This is a post-hoc analysis of the Styrian Vitamin D Hypertension Trial, a single-center, double-blind, randomized, placebo-controlled trial (RCT) performed at the Medical University of Graz, Austria (2011–2014). Two hundred individuals with arterial hypertension and 25-hydroxyvitamin D (25[OH]D) levels <75 nmol/L were randomized to 2800 IU of vitamin D daily or placebo for eight weeks. One hundred ninety-seven participants (60.2 ± 11.1 years; 47% women) were included in this analysis. Vitamin D had no significant effect on bALP (mean treatment effect (MTE) 0.013, 95% CI −0.029 to 0.056 µg/L; p = 0.533), CTX (MTE 0.024, 95% CI −0.163 to 0.210 ng/mL, p = 0.802), OC (MTE 0.020, 95% CI −0.062 to 0.103 ng/mL, p = 0.626), or P1NP (MTE −0.021, 95% CI −0.099 to 0.057 ng/mL, p = 0.597). Analyzing patients with 25(OH)D levels <50 nmol/L separately (n = 74) left results largely unchanged. In hypertensive patients with low 25(OH)D levels, we observed no significant effect of vitamin D supplementation for eight weeks on BTMs.